LC–MS/MS Bioanalysis of Gabapentin in Human Plasma: Method Development, Validation, and Regulatory Perspectives under USFDA and ICH M10 Guidelines - Ashvini Pawar; Shrikrishna Baokar; Rajendra Patil; Mansingh Rajput (Asian Journal of Pharmaceutical Research and Development, 2026)
Gabapentin, a structural analogue of gamma-aminobutyric acid, is widely used in the treatment of epilepsy, neuropathic pain, and related neurological disorders. Reliable quantification of gabapentin in human plasma is critical for pharmacokinetic, bioavailability, and bioequivalence studies. However, due to its high polarity, zwitterionic nature, and lack of strong chromophores, conventional analytical methods such as HPLC and UV spectroscopy often exhibit limited sensitivity and selectivity. In this context, liquid chromatography–tandem mass spectrometry (LC–MS/MS) has emerged as the method of choice for gabapentin bioanalysis owing to its superior sensitivity, selectivity, and robustness. This review provides a comprehensive evaluation of LC–MS/MS methods developed for the quantification of gabapentin in human plasma, with particular emphasis on bioanalytical method development strategies and validation requirements as per United States Food and Drug Administration (USFDA) and International Council for Harmonisation (ICH M10) guidelines. Critical aspects including sample preparation techniques, chromatographic optimization, mass spectrometric parameters, and internal standard selection are systematically discussed. A comparative assessment of reported methods highlights variations in extraction efficiency, matrix effect evaluation, analytical sensitivity, and regulatory compliance. Furthermore, this review identifies key limitations in existing methods, such as inadequate assessment of matrix effects, incomplete stability studies, lack of appropriate internal standards, and insufficient evaluation of carryover, dilution integrity, and incurred sample reanalysis. These gaps may affect the regulatory acceptability and reproducibility of bioanalytical data. In conclusion, although LC–MS/MS offers a highly effective platform for gabapentin bioanalysis, strict adherence to harmonized regulatory guidelines and implementation of a lifecycle-based validation approach are essential to ensure method reliability, reproducibility, and global regulatory acceptance. This review aims to serve as a practical reference for the development of robust and compliant bioanalytical methods for gabapentin.